Downsiders - Shusterman, Neal (New York : Simon & Schuster Books for Young Readers, 1999)
When fourteen-year-old Lindsay meets Talon and discovers the Downsiders world which had evolved from the subway built in New York in 1867 by Alfred Ely Beach, she and her new friend experience the clash of their two cultures